An analysis of word sense disambiguation in Bangla and English using supervised learning and a deep neural network classifier - Pasha, Maroof Ur Rahman (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.